Analysis and design of class E-LCCL compensation circuit topology circuit topology for capacitive power transfer system - Khairul Kamarudin Hasan; Shakir Saat; Yusmarnita Yusop; Masmaria Abdul Majid; Mohd Sufian Ramli (Institute of Advanced Engineering and Science, 2021)
This research introduces the analysis and design of Class E-LCCL for capacitive power transfer (CPT) system. The CPT Class-E LCCL system is able to operate at high-frequency with decreased capacitance plate size and at reduced power losses by minimising switching losses. Additionally, the design of a CPT Class-E LCCL power amplifier is less complicated, since it is usually lighter and smaller with comparative intolerance to different circuit variants; hence, enabling the possibility of miniaturising the system. In this work, the capability of the CPT Class-E LCCL CPT system powered by 24 V DC supply voltage while operating at 1 MHz was analysed via experimental works and extensive simulation. Lastly, a CPT Class-E LCCL system prototype was built, generating 10 W output power via a 0.1 cm air gap at a near-perfect efficiency level of 96.68%. These findings could be beneficial for household apparatus, medical implants, and charging consumer electronics.